Design and construction of diverse mammalian prion strains - Colby, David W. (National Academy of Sciences, 2009)
Prions are infectious proteins that encipher biological information within their conformations; variations in these conformations dictate different prion strains. Toward elucidating the molecular language of prion protein (PrP) conformations, we produced an array of recombinant PrP amyloids with varying conformational stabilities. In mice, the most stable amyloids produced the most stable prion strains that exhibited the longest incubation times, whereas more labile amyloids generated less stable strains and shorter incubation times. The direct relationship between stability and incubation time of prion strains suggests that labile prions are more fit, in that they accumulate more rapidly and thus kill the host faster. Although incubation times can be changed by altering the PrP expression level, PrP sequence, prion dose, or route of inoculation, we report here the ability to modify the incubation time predictably in mice by modulating the prion conformation.